2015
DOI: 10.1002/jcsm.12076
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with skeletal muscle mass, sarcopenia, and sarcopenic obesity in older adults: a multi‐continent study

Abstract: BackgroundThe aim of this study was to evaluate the factors associated with low skeletal muscle mass (SMM), sarcopenia, and sarcopenic obesity using nationally representative samples of people aged ≥65 years from diverse geographical regions of the world.MethodsData were available for 18 363 people aged ≥65 years who participated in the Collaborative Research on Ageing in Europe survey conducted in Finland, Poland, and Spain, and the World Health Organization Study on global AGEing and adult health survey cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
225
3
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(248 citation statements)
references
References 39 publications
(87 reference statements)
13
225
3
7
Order By: Relevance
“…Muscle mass was defined by the Appendicular Muscle Mass (MMA), which is estimated by the sum of the fat-free mass of the arms and legs. The decrease in muscle mass was defined by the Appendicular Muscle Mass Index (IMMA), ratio between MMA and height squared (3,15) . The cutoff point for low muscle mass was 7.26 kg/m 2 in men and 5.45 kg/m 2 in women (15) .…”
Section: Collection and Organization Of Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Muscle mass was defined by the Appendicular Muscle Mass (MMA), which is estimated by the sum of the fat-free mass of the arms and legs. The decrease in muscle mass was defined by the Appendicular Muscle Mass Index (IMMA), ratio between MMA and height squared (3,15) . The cutoff point for low muscle mass was 7.26 kg/m 2 in men and 5.45 kg/m 2 in women (15) .…”
Section: Collection and Organization Of Datamentioning
confidence: 99%
“…The decrease in muscle mass was defined by the Appendicular Muscle Mass Index (IMMA), ratio between MMA and height squared (3,15) . The cutoff point for low muscle mass was 7.26 kg/m 2 in men and 5.45 kg/m 2 in women (15) . Calf circumference (CC) was measured with inelastic tape with the elderly in the upright position, feet 20 cm apart, at the maximum circumference in the plane perpendicular to the longitudinal line of the calf (33) .…”
Section: Collection and Organization Of Datamentioning
confidence: 99%
See 1 more Smart Citation
“…More recently Tyrvolas et al [24] reported a prevalence of sarcopenia of 16.7% in Mexicans over 64 years; two thirds of this being sarcopenic obesity. Sarcopenia associates with impairment [8].…”
Section: Discussionmentioning
confidence: 98%
“…also reported that muscle mass normalized to height‐squared may underestimate sarcopenia particularly in the setting of excess adiposity 4. Sarcopenic obesity was first defined by Baumgartner, who represents a reduced skeletal muscle mass coupled with an increase in fat mass 5, 6, 7. Sarcopenic obesity specifically was highly prevalent among persons with CKD and not those without CKD 8.…”
mentioning
confidence: 99%